First round of targeted biopsies using magnetic resonance imaging/ultrasonography fusion compared with conventional transrectal ultrasonography‐guided biopsies for the diagnosis of localised prostate cancer. (27th July 2014) - Mozer, Pierre; Rouprêt, Morgan; Le Cossec, Chloé; Granger, Benjamin; Comperat, Eva; de Gorski, Arachk; Cussenot, Olivier; Renard‐Penna, Raphaële
<x xml:space="preserve">Abstract</x> Objectives To assess the accuracy of magnetic resonance imaging (MRI)/transrectal ultrasonography (TRUS) fusion to guide first‐round biopsies in the diagnosis of localised prostate cancer (PCa) in men with a prostate‐specific antigen (PSA) ≤10 ng/mL. Patients and Methods A prospective study was conducted on men who met the following criteria: first‐round biopsy, multiparametric MRI (mpMRI) showing a lesion with a Likert score ≥2 and a PSA <10 ng/mL. All men underwent a extended 12‐core protocol plus a protocol of two or three targeted cores on the mpMRI index lesion. The UroStation™ (Koelis, Grenoble, France) and a V10 ultrasound system with an end‐fire three‐dimensional TRUS transducer were used for the fusion imaging procedure. Significant PCa was defined as: at least one core with a Gleason score of 3 + 4 or 6 with a maximum cancer core length ≥4 mm. Results A total of 152 men, whose median PSA level was 6 ng/mL, were included in the study. The proportion of positive cores was significantly higher with the targeted‐core protocol than with the extended 12‐core protocol (P < 0.001). The proportion of men with clinically significant PCa was higher with the targeted‐core protocol than with the extended 12‐core protocol (P = 0.03). The proportion of patients having at least one positive biopsy (targeted‐core protocol) was significantly different among the Likert score categories (P < 0.001). Conclusions For the first round of biopsies, MRI/TRUS‐fusion targeted biopsies detected more men with clinically significant PCa than did standard extended 12‐core biopsy alone.